PENGUATAN SEMANGAT BELAJAR MELALUI PEMBELAJARAN BAHASA ASING - Yusfar Ramadhan; Syaifatul Jannah; Abdul Kirom; Fayruzah el Faradis; Izzat Amini (ABDINA: Jurnal Sosial dan Pengabdian kepada Masyarakat, 2023)
TThis Community Service activity report regarding Strengthening the Spirit of Learning through Foreign Language Learning at the Al-Muniri Islamic Boarding School was conceptualized with guidance on strengthening foreign languages, namely Arabic and English, which is carried out every Wednesday, Thursday and Friday. The background is because the al- Muniri institution was founded under the auspices of the al-Muniri Islamic boarding school, where the students come from santri backgrounds who are not too familiar with foreign languages, especially Arabic itself, but to further improve students' mastery of foreign languages, it is carried out also guidance on strengthening other foreign languages, namely English, because Arabic and English are international languages. This Community Service Activity is carried out using the Asset Based Community Development (ABCD) method. This method aims to develop the assets owned by the village. Through the ABCD method, the assets developed are community assets, namely Al-Muniri Middle School and High School students. The foreign language strengthening guidance process goes through several stages, namely initial deliberations with the teachers, the general person in charge of Al-Muniri School, and the English teacher.